Psychological Trauma, Anxiety, and Depression Among University Students During First Phase of COVID‑19 Movement Control Order in Malaysia - Siti Raudzah, Ghazali; Chen, Yoke Yong; Nur Izzatul Khaleeda, Kasnan; Eleanna Simba, Driver; Nurul Nasriyah, Mahran; Noorain Farihin, Mohd Faezal; Fatin Syakirah, Mohd Fikri; Nurul Aminah, Mohamad Sabuddin (Springer Nature, 2023)
The authors investigated posttraumatic stress disorder (PTSD), anxiety, and depressive symptoms among university students in Malaysia during the COVID-19 pandemic lockdown in a cross-sectional study involving 375 students. Results showed that 39.5% reported PTSD symptoms, 37.3% anxiety symptoms, and 51.4% depressive symptoms. PTSD is significantly correlated with anxiety and depressive symp toms. Female students reported significantly higher PTSD and depressive symptoms. There was a significant association between race, PTSD, and anxiety symptoms. Participants who stayed at residential college (46.2%) and had underlying health problems (70%) reported having significant anxiety symptoms. A significant association between ethnicity and depressive symptoms and underlying health status was also found. The high rates of PTSD, anxiety, and depressive symptoms call for action for mental health promotion and improving mental health delivery services to higher education students in the wake of COVID-19.